Inovasi Pembiayaan Syariah Untuk Mendukung Industri Halal: Studi Kasus di Indonesia - Sri Muliyani; Baso faiz Dzaki; Dwi Reski Febrianti; Kamaruddin Arsyad (TAFAQQUH, 2025)
The development of Islamic financial technology (Islamic fintech) in Indonesia shows significant growth, yet its role in supporting the halal industry ecosystem has not been comprehensively studied. Indonesia, as the country with the world's largest Muslim population, has great potential to optimize the synergy between Islamic fintech and the halal industry. This research aims to analyze the role of Islamic fintech in supporting the development of Indonesia's halal industry ecosystem and identify its impact on Islamic economic growth. The study employs a qualitative approach using systematic literature review (SLR) methodology to analyze 35 literature sources from 2018-2024, including academic journals, government reports, and trusted institutional publications. Islamic fintech has disbursed IDR 9 trillion to SMEs by April 2023 with 440% year-on-year growth in 2021. Indonesia achieved third place globally in the Islamic fintech ecosystem through 17 OJK-licensed platforms. Islamic fintech contributes through mudharabah, musyarakah, murabahah, and ijarah financing schemes, as well as blockchain technology innovation for halal supply chain transparency. Islamic fintech plays a strategic role in creating an integrated halal industry ecosystem through improving SME financing access, digitalizing halal supply chains, and strengthening the competitiveness of Indonesian halal products in the global market with a target contribution of US$5.1 billion to national GDP